First record of Triplax melanocephala (Latreille, 1804) (Coleoptera: Erotylidae) in the cork oak at Collo forest (Algeria) - Laouira, Sabrina; Chakali, Gahdab; Marniche, Faiza (Journal of Agriculture and Applied Biology, 2025)
The Erotylidae family remains poorly documented in North Africa, with very limited published data available on its distribution and ecological preferences. This study provides the first confirmed record of Triplax melanocephala (Latreille, 1804) within Algerian cork oak (Quercus suber) forests, significantly expanding the known range of this species in the region. A total of 71 specimens were documented, collected primarily through soil-surface interception traps deployed across multiple sites. Among these, 25 individuals were captured between 2015 and 2016 in different sections of the surveyed oak groves. Field observations revealed that T. melanocephala exhibits a strong association with decaying cork oak wood, particularly in trees heavily colonized by mature tinder fungi (Fomes spp.). Further investigation through careful dissection of these fungal growths uncovered an additional 30 specimens, reinforcing the species' reliance on this microhabitat. The beetles were most frequently found in moist, shaded areas of decomposing wood, suggesting that microclimatic conditions may play a key role in their distribution. The study sites included Oued Agouf, where 2 specimens were collected in 2015 and 4 in 2016; Ain Fegoum, with 6 specimens in 2015 and 8 in 2016; and El Maktoua, where 4 specimens were recorded in 2015 and 6 in 2016. These findings indicate a consistent presence of T. melanocephala across multiple locations, though population densities varied between sites. This discovery not only fills a gap in the understanding of Erotylidae in North Africa but also highlights the ecological importance of old-growth cork oak forests and their associated fungal communities in supporting specialized beetle fauna.